A rare multiple myeloma complication as a spinal cord metastasis: A case report - Marah Mansour; Zeinab Haider; Lin Al Khiami; Mohammad Saleem Talal Sioufi; Asmaa Takieddin; Aiman Abo Al Shamat; Ricarda Alwaw; Mais Musleh (Clinical Case Reports)
Abstract Multiple myeloma is a hematological cancer mostly located in the marrow of the vertebrae, pelvis, and thighs. Although the presence of extramedullary disease in the central nervous system is rare, herein, we report a complicated case of multiple myeloma in the spinal cord.